Wide range operation of an all-optical NRZ-DPSK-to-RZ-DPSK regenerative waveform-wavelength conversion with exible width-tunability - Irneza Ismail; Quang Nguyen-The; Motoharu Matsuura; Gazi Mohammad Sharif; Naoto Kishi (Optical Society of Japan, 2024)
Indexed by Scopus